Cryptogenic Organizing Pneumonia Complicated With Cutaneous Disseminated Nocardia Infection: A Case Report and Literature Review - Wei, Zhijing; Bao, Pengchen; Wang, Tianle; Wang, Wei; Li, Wen-Yang (Frontiers in Medicine, 2022)
Nocardia disease is a rare opportunistic infection that usually occurs in individuals with solid organ transplantation, malignant tumors, human immunodeficiency virus (HIV) infection, or chronic lung disease history. Here, we reported a rare case of cryptogenic organizing pneumonia (COP) combined with disseminated Nocardia infection. A 75-year-old man was admitted to the respiratory department due to weakness and poor appetite for 3 months. The chest CT scan showed dense patchy shadows in the dorsal lower lobe of both lungs. After the transbronchial lung biopsy, the histopathological findings supported the diagnosis of COP. During the period of glucocorticoid reduction (oral methylprednisolone tablets 24 mg one time a day), the patient presented with masses on the back and bilateral upper limbs and intermittent fever for 3 days. After admission, the patient underwent a series of examinations and an ultrasound puncture of the mass. The puncture fluid was caseous necrosis, which was confirmed to be Nocardia infection after bacterial culture, so the diagnosis was disseminated Nocardia infection. After 13 days of admission, the patient developed a headache, accompanied by decreased visual acuity and blurred vision. An imaging (enhanced brain CT) examination revealed intracranial space-occupying lesions. The neurosurgeon was consulted and performed transcranial abscess puncture and drainage, intravenous antibiotics (meropenem, etc.) for 2 months, and trimethoprim/sulfamethoxazole (TMP-SMX) for 6 months. The patient was followed up for 3 years and has remained relapse-free. The mortality rate of disseminated Nocardia infection is as high as 85%, especially when combined with brain abscesses. Therefore, timely diagnosis and correct treatment are crucial for the prevention of fatal consequences. The report of this case can enable more patients to receive early diagnosis and effective treatment, so as to obtain a satisfied prognosis.